Comparative study Of Absolute Strength and EMG of Weightlifter’s Arms and Legs Muscles - Abdul-Hassan, Ghassan Adeeb; Mahdi, Mustafa Salih; Hadi , Ali Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Comparative study Of Absolute Strength and EMG of Weightlifter’s Arms and Legs Muscles are attitudes and factors that affect maximum strength training one of these factors is the size of the muscle. The researcher compared the size of arms and legs muscles from the absolute strength point of view. The research aimed at : 1- Identifying the differences between arms and legs muscles in absolute strength of weightlifters. The researcher selected a random sample from the students of physical education and sport sciences/ university of Baghdad. The subjects were (6) weightlifters. Absolute strength tests were conducted on arms and legs. The data was collected and treated using SPSS. The researcher concluded that arm muscles were higher in absolute strength compared to legs. He finally recommended the necessity of using EMG for developing absolute strength in muscles.